Expression of Cathepsins B, D, and G in Infantile Hemangioma - Itinteang, Tinte; Chudakova, Daria A.; Dunne, Jonathan C.; Davis, Paul F.; Tan, Swee T. (Frontiers in Surgery, 2015)
Aims: The role of the renin-angiotensin system (RAS) in the biology of infantile hemangioma (IH) represents an emerging paradigm, particularly the involvement of renin, angiotensin converting enzyme and angiotensin II. This study investigated the expression of cathepsins B, D and G, enzymes that may modulate the RAS, in IH. Materials and Methods: The expression of cathepsins B, D and G was examined using immunohistochemistry, enzyme activity assays, mass spectrometry and Nanostring gene expression assay in IH samples at different phases of development. Results: Immunohistochemical staining showed the expression of cathepsins B, D and G in proliferating and involuted IH samples. This was confirmed at the transcriptional level using Nanostring gene expression assays. Mass spectrometry confirmed identification of cathepsins D and G in all three phases of IH development, whereas cathepsin B was detected in 2/2 proliferating and 1/2 involuting lesions. Enzyme activity assays demonstrated the activity of cathepsins B and D, but not G, in all phases of IH development. Conclusions: Our data demonstrated the presence of cathepsins B, D and G in IH. Their role in modulating the RAS and the biology of IH offers potential novel targets for the management of this tumor.